Analysis of dominant physical factors in volleyball skills: confirmatory analysis of the Bahana Muda volleyball team - Mahesa Dwi Chandra (CV Rezki Media, 2025)
Background: Physical condition is an important determinant of volleyball skill performance, but few studies have empirically tested the structure of its dominant factors using a confirmatory approach. Objectives: This study aims to identify the dominant physical condition factors that influence the playing skills of Bahana Muda Club volleyball athletes using Confirmatory Factor Analysis (CFA). Methods: This study used a quantitative descriptive design. The sample consisted of 20 male volleyball athletes from the Bahana Muda Club who were selected through purposive sampling. The physical condition variables measured included speed (30-meter run), endurance (beep test), arm muscle strength (push-ups), abdominal muscle strength (sit-ups), leg muscle power (vertical jump), and agility (shuttle run). The analysis was conducted through an initial exploratory analysis and continued with CFA using IBM SPSS AMOS version 26. The goodness-of-fit model was evaluated using the CFI, TLI, and RMSEA indices. Results: The CFA results show that leg muscle power (λ = 0.791), arm muscle strength (λ = 0.742), endurance (λ = 0.732), and agility (λ = 0.606) have significant factor loadings on volleyball skills (p < 0.05), while abdominal muscle speed and strength did not show significant contributions. The CFA model showed good data fit (CFI = 0.986; TLI = 0.978; RMSEA = 0.050). Conclusions: Leg muscle power, arm muscle strength, endurance, and agility are the dominant physical factors in volleyball skills. Training programs should prioritize these components, and further research should involve larger samples and cross-clubs.